Al-Nuʿmān ibn al-Mundhir (580–602 CE) Authoritarian Power in the Context of the Tribal State and Regional Balances - Prof. Dr. Saad Aboud Sammar (Journal of College of Education, 2025)
Al-Nuʿmān ibn al-Mundhir is regarded as one of the most controversial figures in pre-Islamic Arab history, due to the complexity of his political position and the duality of his cultural and religious affiliations. He functioned as an intermediary king between the Sasanian Empire and the Arabs, while simultaneously preserving the features of Arab leadership. He also engaged in a multifaceted symbolic struggle with poets and with rival tribes.The reign of al-Nuʿmān ibn al-Mundhir constituted a significant phase in the history of pre-Islamic Arab political authority. The Kingdom of al-Ḥīra was characterized by distinctive authoritarian features that combined loyalty to the Sasanians with the employment of ritual symbolism to consolidate power. This was clearly reflected in al-Nuʿmān’s personal practices, which blended symbolic and physical violence and employed bloody political rituals to reinforce his prestige and authority.What makes al-Nuʿmān a particularly rich subject for study is the close association of his power with violent rituals and forms of political spectacle that went beyond conventional violence to symbolic violence. This is evident in events such as the “Day of Misfortune” and the “Day of Bliss,” as well as in the construction of the “al-Gharīyayn,” among other acts that cannot be understood except through a complex psycho-social analysis.The significance of this research lies in its illumination of a rare intersection between the political-historical context and the psychological structure of the authoritarian ruler’s personality in pre-Islamic Arab culture. This approach enables a deeper understanding of the nature of authority in Arab society—not merely as direct governance, but as a symbolic system charged with religion, violence, and fluctuating loyalties.
Keywords: Al-Nuʿmān b. Al-Mundhir; tyranny; pre-Islamic Arabian history